Gender as a factor influencing the frequency of meat and fish consumption in young adults - Joanna Frąckiewicz; Zuzanna Sawejko; Anna Ciecierska; Małgorzata Ewa Drywień (Roczniki Panstwowego Zakladu Higieny, 2023)
Background. Meat and fish contain easily digestible whole protein, B vitamins and numerous minerals, such as zinc, phosphorus and iron, thanks to which these products have a high nutritional value. Objective. The aim of the study was to assess the frequency of consumption of meat and fish in young adults depending on gender. Material and Methods. Data was collected from 200 respondents aged 19-30 using online survey questionnaire. The questionnaire was divided into three parts. The first part contained questions about sociodemographic and anthropometric data, the second part contained a question regarding the self-assessment of the diet. Whereas, the third part of the questionnaire concerned the frequency of consumption of meat and fish. Statistical analysis of the results was performed using Statistica 13.3 software and statistical significance was assumed at the p≤0.05 level. Results. Meat consumption was declared by 86.5% of the respondents (83% of women and 90% of men), usually 5-6 times a week (20%). Gender statistically significantly differentiated the frequency of meat consumption. Men significantly more often consumed total meat (p=0.002), red meat (p=0.001) and poultry (p=0.004) compared to women. Fish was eaten by 85% of the respondents, and 39% only 1-3 times a month. Respondents preferred oily fish. There were no statistically significant differences in the consumption of fish by men and women. Conclusions. Considering the complexity of the relationship between men and women’s meat and fish consumption and health, research is needed to clarify the amounts of meat and fish consumed, the degrees and how they are processed, and the reasons for eating or not eating them. This can be helpful in directions for nutritional education.